Retorika Krisis: Analisis Pidato Presiden Indonesia dan Korea Selatan pada Tragedi Kanjuruhan dan Itaewon - Kezia Sola Gratia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study compares the responses of the Indonesian and South Korean presidents to man-made disasters and investigates the presence of shift-blaming in their speeches. Utilizing Rhetorical Analysis (RA) to examine how speeches are constructed to achieve specific objectives, and Critical Discourse Analysis (CDA) to explore historical and social contexts, the study focuses on President Jokowi’s speeches following the Kanjuruhan tragedy and President Yoon’s speeches after the Itaewon disaster. RA delves into the rhetorical strategies, including invention, disposition, style, and delivery, to analyze how each president uses ethos, logos, and pathos to construct their messages. CDA further examines the discourse of shift-blaming characteristic of autocratic tendencies. The findings reveal differences in how each president addresses responsibility and accountability. While the trace of shift blaming is prominently evident in Jokowi’s speeches, Yoon’s speeches are characterized by a strong emphasis on image-saving. This comparative analysis provides insights into the distinct communication strategies employed by leaders in response to man-made disasters.